PERSEPSI GURU EKONOMI DI SMA NEGERI KOTA PONTIANAK SELATAN TENTANG KURIKULUM 2013 - Ramadan, Wahyu; Mashudi, Mashudi; Buwono, Sri (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe purpose of this research is to study (1) the perception of economics teacher of Senior High School in South Pontianak City about the Competency Standard of graduates of curriculum 2013. (2) perception of economics teacher of Senior High School in South Pontianak about standard of curriculum content of 2013. (3) South Pontianak City on Standard of Curriculum Process 2013. (4) Perception of Senior High School Economics teacher in South Pontianak City on Curriculum Values Standards 2013. This research uses descriptive methodology, in qualitative research. Respondents include economics subject teachers and Vice Head of Senior High School curriculum in South Pontianak, whose schools have applied the 2013 curriculum. The results of this research are: (1) teachers have positive responses on attitude and skill aspect become the standard of graduation because education should besides create smart students too (2) there is a change in the standard of content that incriminates the teacher is the change of Basic Competence, accounting material is charged in class 12, consequently teacher difficulty maximizing Basic Competence achievement, (3) The teacher understands the changes in the standards of the 2013 curriculum process that is in the lesson plan and the learning method, (4) the teacher understands the changes. The curriculum assessment standard 2013 is on attitude assessment only given by the teachers of religion and PPKn, and the assessment of knowledge is returned to scale 1-100. Keywords: Persepi, 2013 curriculum (SKL, Content Standards, Process Standards, Assessment Standards).